Deteksi Keausan Alat pada Proses Pengeboran Sumber Alam - Siana Halim; Felecia . (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2012)
In this paper we applied change point detection methods for failures detection in the drilling process. We calculated the change points on three drilling parameters, i.e., the weight on bit, top drive torque and rate of penetration. Using the concept of reliability, we measured the time between change points as the time between failures. The minimum of mean time between change points from those three parameters is suggested to be the time for monitoring the drilling process.